1992
DOI: 10.1007/bf00168943
|View full text |Cite
|
Sign up to set email alerts
|

The release of dopamine from nerve terminals and dendrites of nigrostriatal neurons induced by excitatory amino acids in the conscious rat

Abstract: The possible localization of excitatory amino acid (EAA) receptors on dopaminergic neurons was studied by microdialysis in conscious male rats. Varying concentrations of 3 specific EAA agonists, N-methyl-D-aspartate (NMDA), kainate and amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA), were infused into the striatum or into the substantia nigra, and the extracellular dopamine (DA) was recorded by the same probe. All 3 compounds induced a dose-dependent increase in both striatal and nigral extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(64 citation statements)
references
References 19 publications
10
53
1
Order By: Relevance
“…At higher concentrations (10-5 to 10-3 mollL), this effect was reversed, with DA release being decreased Leviel et al 1990). In vivo microdialysis experiments also support the facili tation of striatal DA release following a local injection of excitatory amino acids (Westerink et al 1992, Keefe et al 1992, although depression of DA release was not observed even at the highest concentrations used (1 mmol AMP A, 1 mmol N-methyl-D-aspartate, 0.1 mM kainate). These results show primarily, although not exclusively, facilitatory actions of glutamate on DA re lease in the striatum.…”
Section: Electrical Stimulation Of the Medial Prefrontal Cortex Incrementioning
confidence: 59%
“…At higher concentrations (10-5 to 10-3 mollL), this effect was reversed, with DA release being decreased Leviel et al 1990). In vivo microdialysis experiments also support the facili tation of striatal DA release following a local injection of excitatory amino acids (Westerink et al 1992, Keefe et al 1992, although depression of DA release was not observed even at the highest concentrations used (1 mmol AMP A, 1 mmol N-methyl-D-aspartate, 0.1 mM kainate). These results show primarily, although not exclusively, facilitatory actions of glutamate on DA re lease in the striatum.…”
Section: Electrical Stimulation Of the Medial Prefrontal Cortex Incrementioning
confidence: 59%
“…Rather, D4Rs are densely localized on glutamatergic pyramidal cells of frontal cortex (Mrzljak et al, 1996;Ariano et al, 1997;Rubinstein et al, 1997) that project to the dorsal striatum and the substantia nigra (Carter, 1982). The stimulation of nigrostriatal nerve terminals (Westerink et al, 1992) in the dorsal striatum or of nigral neurons by glutamate induces dopamine release (Overton and Clark, 1992). Accordingly, dopamine synthesis and its conversion to DOPAC are increased in the dorsal striatum of D4RϪ/Ϫ mice (Rubinstein et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Another may be differences in the manner in which glutamate, released by these antagonists, may stimulate the release of dopamine in the PFC versus the striatum. Previous studies investigating this interaction indicate that stimulation of kainate or AMPA receptors is much more potent in increasing dopamine release in the PFC as compared with the striatum (Westerink et al, 1992;Jedema and Moghaddam, 1996).…”
Section: Mechanism By Which Ketamine Increases Dopamine Release In Thmentioning
confidence: 93%